Association Between Social Support and Perceived Stress: A Cross-Sectional Study on Staffs of the Epidemic Prevention During the Covid-19 Epidemic in China - Zhang, Ling; Fu, Binbin; Xu, Yi; Zhang, Qi; Peng, Shuzhen; Tan, Xiaodong (Frontiers in Public Health, 2022)
Background: The Coronavirus Disease 2019 (COVID-19) lockdown considerably affects people’s life in China, both physically and mentally. During lockdown period in Wuhan, staffs of the epidemic prevention and control in the community have played an irreplaceable role. This study attempted to study the mental states of them and explore the influencing factors. Method: Used a multistage sampling method, we conducted a survey in staffs of the epidemic prevention and control in the community(N=503). Descriptive analysis was used to characterize the respondents. Confirmatory factor analysis (CFA) was used to verify the factor validity and Structural equation model (SEM) was used to study the relationship between stress perception, social support, mental resilience and sleep quality. Statistical analysis was performed with SPSS 26.0 and Mplus 8.3. Results: The mean PSS score of the respondents was 13.27±7.31 and 51.1% had higher PSS score than the normal. In the absence of social support, people’s sleeping quality and self-regulation ability may decrease, their perceived stress may elevate and compromise mental health correspondingly. Social support could affect perceived stress directly, while sleep quality and psychology resilience were significant mediators between social support and perceived stress. The mediating effects accounted for 42.5% of the total. Conclusion: Staffs of the epidemic prevention and control in the community suffered from poor sleep quality and high level of stress perception. Establishment of good social support may effectively improve their sleep quality and flourish mental health.